2014
DOI: 10.3122/jabfm.2014.06.140108
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Health (mHealth) Tools by Primary Care Patients in the WWAMI Region Practice and Research Network (WPRN)

Abstract: Purpose The purpose of this study was to determine the prevalence of mobile health (mHealth) use among primary care patients and examine demographic and clinical correlates. Methods Adult patients who presented to 1 of 6 primary care clinics in a practice-based research network in the northwest United States during a 2-week period received a survey that assessed smart-phone ownership; mHealth use; sociodemographic characteristics (age, sex, race/ethnicity, health literacy); chronic conditions; and depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 13 publications
5
40
0
Order By: Relevance
“…16 As is typical of primary care patients, a majority of participants were female (75%), and many had health literacy limitations (62%), chronic medical conditions (63%), and current depressive symptoms (21%). Participants spanned a range of ages (range: 18–94 years; 15% 18–24 years, 21% 25–34 years, 19% 35–44 years, 19% 45–54 years, 16% 55–64 years, 9% 65 years or greater; mean = 42.7 years; SD = 15.9 years) and ethnicities (80% non-Hispanic white, 5% Hispanic or Latino, 4% Asian American/Pacific Islander, 2% African American, 9% American Indian/Alaska Native or multiracial/other).…”
Section: Resultsmentioning
confidence: 99%
“…16 As is typical of primary care patients, a majority of participants were female (75%), and many had health literacy limitations (62%), chronic medical conditions (63%), and current depressive symptoms (21%). Participants spanned a range of ages (range: 18–94 years; 15% 18–24 years, 21% 25–34 years, 19% 35–44 years, 19% 45–54 years, 16% 55–64 years, 9% 65 years or greater; mean = 42.7 years; SD = 15.9 years) and ethnicities (80% non-Hispanic white, 5% Hispanic or Latino, 4% Asian American/Pacific Islander, 2% African American, 9% American Indian/Alaska Native or multiracial/other).…”
Section: Resultsmentioning
confidence: 99%
“…9 In only 5 years, mHealth has grown into a billion-dollar industry. 10 Smartphone ownership has markedly increased every year since 2008, with the prevalence of smartphone ownership in the general population increasing from 35% to 56% from 2011 to 2013. 11 We previously demonstrated that kidney transplant patients thought that mHealth provided a platform for self-efficacy and improved medical management.…”
mentioning
confidence: 99%
“…26 Access to smartphones was 1 of the least commonly cited barriers, which corresponds to a recent study indicating that 55% of primary care patients use smartphones, and 70% of those patients with smartphones use them for health-related purposes. 27 An additional potential barrier to studies involving technology-based patient engagement strategies is clinician acceptance. Clinician acceptance is critical to the successful recruitment of practices and has been found to facilitate study implementation.…”
Section: Discussionmentioning
confidence: 99%